MALDI-TOF MS Identification and Clustering Applied to Enterobacter Species in Nosocomial Setting - De Florio, Lucia; Riva, Elisabetta; Giona, Annalisa; Dedej, Etleva; Fogolari, Marta; Cella, Eleonora; Spoto, Silvia; Lai, Alessia; Zehender, Gianguglielmo; Ciccozzi, Massimo; Angeletti, Silvia (Frontiers in Microbiology, 2018)
Enterobacter microorganisms cause important bacterial infections in humans. Recently, carbapenem resistant isolates carrying the blaKPC gene were described and their clonal transmission in different nosocomial outbreaks reported. In this study, the relative numbers of Enterobacter species, their antimicrobial susceptibility along three years of observation and the identification ability of the two most common MALDI-TOF platforms were evaluated. A clustering analysis was performed to identify changes in the microbial population within the nosocomial environment. Enterobacter were identified using two platforms (MALDI-TOF Biotyper and VITEK MS. Antimicrobial susceptibility was tested by Vitek2 Compact and MIC50 and MIC90 was evaluated using GraphPad software. Clustering analysis was performed by MALDI-TOF and a dendrogram was built with both platforms and compared. The most frequent species isolated were Enterobacter cloacae and Enterobacter aerogenes with a gradual increase of Enterobacter asburiae in 2017. MALDI-TOF platforms showed a very good sensitivity and specificity except for E. asburiae identification that was reliable only by MALDI-TOF MS Biotyper. An increase of resistance for Enterobacter, confirmed by the isolation of ESBL strains and the emergence of Enterobacter cloacae MDR and carbapenem resistant strains, was observed. A clonal route of transmission involving general surgery and geriatric wards was evidenced as previously described for Klebsiella pneumoniae MDR strains in the same nosocomial setting. These data represent an important source of information about the spreading of Enterobacter in the nosocomial environment.